Stage-dependent changes in culture medium osmolality promote porcine oocyte maturation in vitro - Liu, Lixiang; Tang, Yu; Shao, Jing; Fan, Bingfeng; Yang, Yifeng; Zhang, Ying; Zhao, Xiangyuan; Xue, Hailong; Sun, Huimin; Zhang, Xulin; Zhang, Yushi; Xu, Baozeng (Frontiers in Cell and Developmental Biology, 2025)
IntroductionEarly preimplantation embryos of mammals exhibit pronounced sensitivity to hyperosmotic conditions, which results in an embryonic developmental block. The reduction of medium osmolarity or the supplementation with organic osmolytes can eliminate this arrest. Therefore, cell volume homeostasis is essential for embryonic development in vitro. Oocytes become capable of independent volume regulation after detaching from the follicle microenvironment. Whether the efficiency and quality of oocyte maturation can be improved by optimizing cell volume regulation by adjusting the osmolality of the culture medium in the presence of the organic osmolyte of glycine remains to be determined.MethodsThe IVM of porcine oocytes was divided into two stages, i.e. the first 22 h as the first stage, and the last 22 h as the second stage. In the presence of 1 mM glycine, we adjusted the osmolality of the culture medium from low to high (290 mOsM for the first 22 h and 320 mOsM thereafter) by adding raffinose, which cannot be used by animal cells, in a culture stage-dependent manner.ResultsStage-dependent adjustment of simplified medium PZM-3 osmolarity (290 mOsM for the first 22 h and 320 mOsM thereafter) in the presence of 1 mM glycine significantly improved the quality of porcine oocyte maturation in vitro, manifested by the oocyte maturation rate, functional mitochondrial distribution and activity, the transcript levels of glycolysis genes in granulosa cells, and subsequent embryonic developmental ability and ROS levels.ConclusionOur study demonstrates that optimizing cell volume regulation can further enhance the developmental potential of oocytes cultured in vitro.